Coordination polymers of Fe(III) and Al(III) ions with TCA ligand: distinctive fluorescence, CO2 uptake, redox-activity and oxygen evolution reaction - Dhara, Barun; Sappati, Subrahmanyam; Singh, Santosh K.; Kurungot, Sreekumar; Ghosh, Prasenjit; Ballav, Nirmalya (Dalton Transactions, 2016)
Fe and Al belong to different groups in the periodic table, one from the p-block and the other from the d-block. In spite of their different groups, they have the similarity of exhibiting a stable 3+ oxidation state. Here we have prepared Fe(III) and Al(III) based coordination polymers in the form of metal-organic gels with the 4,4', 4 `'-tricarboxyltriphenylamine (TCA) ligand, namely Fe-TCA and Al-TCA, and evaluated some important physicochemical properties. Specifically, the electrical conductivity, redox-activity, porosity, and electrocatalytic activity (oxygen evolution reaction) of the Fe-TCA system were noted to be remarkably higher than those of the Al-TCA system. As for the photophysical properties, almost complete quenching of the fluorescence originating from TCA was observed in case of the Fe-TCA system, whereas for the Al-TCA system a significant retention of fluorescence with red-shifted emission was observed. Quantum mechanical calculations based on density functional theory (DFT) were performed to unravel the origin of such discriminative behaviour of these coordination polymer systems.

Cisplatin-induced self-assembly of graphene oxide sheets into spherical nanoparticles for damaging sub-cellular DNA - Nandi, Aditi; Mallick, Abhik; More, Piyush; Sengupta, Poulomi; Ballav, Nirmalya; Basu, Sudipta (Chemical Communications, 2017)
This report describes the hitherto unobserved cisplatin induced self-assembly of 2D-graphene oxide sheets into 3D-spherical nano-scale particles. These nanoparticles can encompass dual DNA damaging drugs simultaneously. A combination of confocal microscopy, gel electrophoresis and flow cytometry studies clearly demonstrated that these novel nanoparticles can internalize into cancer cells by endocytosis, localize into lysosomes, and damage DNA, leading to apoptosis. Cell viability assays indicated that these nanoparticles were more cytotoxic towards cancer cells compared to healthy cells.